1-year hospital readmissions due to cardiovascular causes after a heart failure episode in elderly patients in Spain. (3rd October 2022) - Esteban Fernandez, A; Anguita, M; Bonilla, J L; Anguita, M; Ruesgas, R; Molina, M; Garcia, M; Bernal, J L; Del Prado, N; Fernandez Perez, C; Marin, F; Perez Villacastin, J; et al.
Abstract: Background: The prevalence of heart failure (HF) increases with age, one of the leading causes of hospitalization and death in the elderly. However, there are little data about the long-term readmission rate of elderly patients after an episode of HF admission in Spain. Purpose: Study 1-year hospital readmissions due to cardiovascular causes in patients ≥75 years discharged to a hospital due to HF in Spain. Methods: We performed a retrospective analysis of the Minumum basic dataset of Spain, including all episodes of HF discharged from public hospitals in Spain between 2016 and 2019. The codification was made with ICD-10. We selected patients ≥75 years with HF as the principal diagnosis. We analyzed predictors of readmissions 365 days after the index episode of HF hospitalization with Poisson regression. Results: 236, 463 index episodes of HF in>75 years were included. 59.1% were female, and the mean age was 85 (SD 5.6) years. 35.0% had HF-pef, 4.3% HF-ref, and 60.7% had unknown LVEF HF. 39.6% of patients had at least one readmission (mean 1.7 readmissions by year for these patients), with no differences in sex or age. Patients with non-cardiovascular comorbidities (renal failure, chronic lung disorders, and severe hematological disorders) as well as coronary atherosclerosis and diabetes were more likely to be readmitted (Table 1). Conclusions: After a hospital discharge for HF in patients ≥75 years, the crude ratio of readmission due to cardiovascular causes at 1-year was 39.6%. Readmissions were more likely in patients with non-cardiovascular comorbidities, predominantly renal, hematological, and chronic respiratory disorders, and those with diabetes and coronary atherosclerosis. Funding Acknowledgement: Type of funding sources: None.